Acetyl genistin modulates myotube differentiation and attenuates dexamethasone-induced muscle atrophy through the FoxO1/3 signaling pathway in C2C12 myotubes - Won Min Jeong; Seung-Jin Kwag; Jun Young Ha; Seung-Jun Lee; Yeong-In Choe; Dong Yeol Lee; Dong Kyu Jeong; Hwan Hee Bae; Jin-Hee Seo; Young-Sool Hah; Sang Gon Kim (Applied Biological Chemistry, 2024)
Abstract Muscle atrophy, a debilitating condition characterized by loss of muscle mass and strength, is a major concern in various clinical settings. Acetyl genistin (AG), a bioactive compound, was evaluated for its role in muscle cell differentiation and its potential protective effects against dexamethasone (dexa)-induced muscle atrophy. Our study demonstrated that AG significantly promoted C2C12 myotube differentiation, as evidenced by enhanced myotube width and increased fusion index. Notably, AG treatment upregulated the expression of myogenic markers, including MHC, MyoD, and MyoG. Moreover, AG displayed protective properties by attenuating dexa-induced muscle atrophy, mainly by suppressing the expression of the atrophy-related genes MAFbx and MuRF1. AG's protective effects are mechanistically attributed to its regulation of the AMPK/FoxO-dependent signaling pathway. Our results highlighted the dual benefits of AG in fostering muscle differentiation and safeguarding against muscle atrophy, positioning it as a promising agent for muscle health and therapeutic applications.